2013
DOI: 10.1152/physiolgenomics.00139.2011
|View full text |Cite
|
Sign up to set email alerts
|

Identification of gene sets and pathways associated with lactation performance in mice

Abstract: -Mammary transcriptome analyses across the lactation cycle and transgenic animal studies have identified candidate genes for mammogenesis, lactogenesis and involution; however, there is a lack of information on pathways that contribute to lactation performance. Previously we have shown significant differences in lactation performance, mammary gland histology, and gene expression profiles during lactation [lactation day 9 (L9)] between CBA/CaH (CBA) and the superior performing QSi5 strains of mice. In the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 80 publications
0
14
0
Order By: Relevance
“…These significantly enriched biological pathways provided important information on the mechanism of DQP. Many of these enriched pathways have been associated with HF, e.g., the importance of neuroactive ligand–receptor interaction in the development and progress of cardiovascular diseases [26]. The key proteins in this pathway, such as adrenergic, angiotensin, and calcitonin receptor-like neurotensin receptors, are closely related to cardiac function [27-29].…”
Section: Resultsmentioning
confidence: 99%
“…These significantly enriched biological pathways provided important information on the mechanism of DQP. Many of these enriched pathways have been associated with HF, e.g., the importance of neuroactive ligand–receptor interaction in the development and progress of cardiovascular diseases [26]. The key proteins in this pathway, such as adrenergic, angiotensin, and calcitonin receptor-like neurotensin receptors, are closely related to cardiac function [27-29].…”
Section: Resultsmentioning
confidence: 99%
“…Overall, some of the identified GO and KEGG categories have been previously detected in gene-set enrichment studies using the individual CF t , CY, and REC phenotypes (Dadousis et al, 2016), milk yield traits (Iso-Touru et al, 2016), or gene expression studies of the mammary gland in mice (Ramanathan et al, 2008;Wei et al, 2013) and humans (Maningat et al, 2009).…”
Section: Gene-set Enrichment and Pathway Analysismentioning
confidence: 90%
“…Some of these terms have been previously connected with milk production in mice. More precisely, the GO _BP: 0006811 (ion transport), GO _MF: 0005216 (ion channel activity), GO_MF: 0022838 (substrate-specific channel activity), and GO _MF: 0015267 (channel activity) were upregulated in mice with increased milk yield (Wei et al, 2013). Moreover, it is known that in the cheese process the caseins react with calcium ions.…”
Section: Gene-set Enrichment and Pathway Analysismentioning
confidence: 99%
“…Significantly, in the current study, pathway enrichment results indicated that genes in key modules 1, 2, 3, 5, 6, and 7 were simultaneously enriched in the pathway of neuroactive ligand-receptor interaction. As documented, the pathway of neuroactive ligand-receptor interaction has been demonstrated to be associated with the development and progress of cardiovascular diseases [ 46 ]. The key proteins in this pathway, such as angiotensin, adrenergic, and calcitonin receptor-like neurotensin receptors, have also been indicated to be closely related to cardiac function [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%